Retrograde Positive Contrast Urethrocystography of the Fish Urogenital System - Francesco Macrì; Annamaria Passantino; Michela Pugliese; Simona Di Pietro; Daniele Zaccone; Pietro Giorgianni; Rossella Bonfiglio; Fabio Marino (The Scientific World Journal)
The radiological differences between the urinary tract of  Dicentrarchus labrax, Sparus aurata, Tinca tinca, and Cyprinus carpio are shown. In fresh water teleosts the urinary bladder is sigmoid and a short urethra leads to the urinary pore. Genital and anal pores are present. In Sparus aurata the urinary bladder has a globoid shape. In Dicentrarchus labrax the urinary bladder is smaller and elongate. In both marine teleosts a single urogenital pore is visible. Positive contrast was used to survey the urogenital system and evaluate shape and size of the bladder, urethra, ureter, and gonadal ducts. Results demonstrate the morphological variability of the urinary bladder and the craniodorsal entry of the ureters into the bladder. It is envisaged that this work will provide baseline information for further imaging studies for investigating the urogenital morphology and can be applied to identify disorders in fishes. Furthermore, the main interest of this study is that it demonstrates the morphological variability of the lower urinary system that exists between different species of fishes.